Therapeutic embolisation of the external carotid arterial tree. - Kendall, B (1977)
Intra-arterial embolisation is a valuable adjunct to the treatment of many vascular lesions, including neoplasms such as glomus tumours or juvenile angiofibromas, and arteriovenous malformations. Its place in the management of the individual patient should be established before any surgical procedure is carried out, as this may prejudice the eventual result. The indications for the procedure, the technique, and possible complications are discussed in this paper, and it is emphasised that the latter are best avoided by the use of a scrupulous technique and adequate technical facilities.